Violence Against Women And Its Strategic Role In Covid-19 Control - Revency Vania Rugebregt (Faculty of Law, Pattimura University, 2022)
Violence against women does not only mean physical violence. It is broader and includes sexual, emotional, psychological and financial issues. In fact, in real life women make a lot of positive contributions so that the terms women entrepreneurs, smart women, heroines, and so on are known. Finally, women are still considered and valued negatively in meaning. Moreover, with the patriarchal culture that dominates in Indonesia, women are often the object of violence and complement the sufferers of men. This study used the method of normative. It is called juridical-normative because this paper was aimed to explore the principles of law to solve the problems that would be studied in this paper. The data used was secondary data, in the form of an inventory of positive legal norms in force in Indonesia governing the civil rights of illegitimate children and children's rights. The data was analyzed using qualitative analysis.